As provas de matemática do ENEM: conteúdos, dificuldades e influências para o currículo do ensino - Deleprani, Marcio (2012)
The work is a study defined from investigations in the process of evaluation of the pupils through the tests of the National Examination of Average Ensino (Enem), the work also evaluates the test as instrument that guides the composition of the resume of average education and as an instrument that democratizes the access to superior education. The research was directed to guide professors and pupils of as the test of the Enem is organized and also to alert educators on the level of requirement of this test, that has as one of its objectives, to democratize the access to superior education. The general objective of the work was to analyze questions of mathematics of the test of the Enem and to define its degree of difficulty and then to verify if this only test can be one of the only ways of access to superior education. As it has supported the research presented divided theoretical referencial in two axles. The first axle was to search given and to have an information statistics of the situation of the pupils in Brazil and to collate them with the data of the tests and as it was to verify the opinion of educators on as they would have to be the mathematics education. The inquiry was carried through with the questions of mathematics in editions of 2009, 2010 and 2011, the tests had been removed of the site of the National Institute of Studies and Educational Research Anísio Teixeira (Inep) and its contents had been compared with the minimum resume of the average education of the state of Rio de Janeiro. The analysis of the data showed that the current levels of the test of the Enem and the pupils of the public nets of education need to improve.